Experiences of innovation in public services for sustainable urban mobility - Silvia Stuchi Cruz; Sônia Regina Paulino (Journal of Urban Management, 2022)
The article aims to analyze non-motorized transport initiatives by adopting the innovation-in-services approach based on multi-agents. We selected ten cases in the municipality of Sao Paulo, Brazil. Our findings identified innovations in the local context in the treatment of infrastructure for active mobility. These public services were introduced in a participatory process and a collective re-appropriation of urban space. Innovation is based on techniques and competences. The projects promote an expansion of the competences of service providers related to interactions with civil society, resulting in an integral perspective on the uses, local dynamics and behavioral issues of the users themselves. Service provider techniques are temporary and permanent intervention methodologies, and methodologies for project impact evaluation. These techniques are associated with tactical urbanism for temporary urban interventions. User techniques were identified to apply the propensity score-matching method, which aims to evaluate the impacts of an instance of intervention through the comparison of groups in addition to technical inspections and local interviews. The relationship management generated relational and organizational competences for civil society organizations. Therefore, public services for non-motorized transportation have a great deal of potential to shape innovations, following transformations intended for a sustainable urban mobility paradigm.
Keywords: 710; Active mobility; Brazil; Innovation in services; Public sector innovation; Public services